2019
DOI: 10.21037/atm.2018.10.65
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage hybrid localization: a combination of bronchoscopic lung mapping followed by post-mapping computed tomographic reconstruction and additional transthoracic needle localization in a cone beam computed tomography room

Abstract: Background: Bronchoscopic lung mapping is a multispot dye-marking technique, which should be performed under real-time fluoroscopic guidance and post-mapping computed tomographic reconstruction. This study aimed to investigate the feasibility of lung mapping followed by post-mapping computed tomography (CT) and additional needle localization in a cone bean CT (CBCT) room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Several studies have reported that severe radiation injuries can occur because of prolonged interventional procedures (Krim et al 2011, Padovani et al 2011, Sun et al 2013. Although the effectiveness of AFB has been demonstrated in numerous clinical cases (Fang et al 2019, Yang et al 2019a, 2020b, no evaluation of patients' and medical staff 's exposure to radiation during these procedures has been performed. The present study evaluated the skin and effective doses received by patients and the personal dose equivalent to the eye lens [H p (3)] of physicians during AFB procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that severe radiation injuries can occur because of prolonged interventional procedures (Krim et al 2011, Padovani et al 2011, Sun et al 2013. Although the effectiveness of AFB has been demonstrated in numerous clinical cases (Fang et al 2019, Yang et al 2019a, 2020b, no evaluation of patients' and medical staff 's exposure to radiation during these procedures has been performed. The present study evaluated the skin and effective doses received by patients and the personal dose equivalent to the eye lens [H p (3)] of physicians during AFB procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the cone-beam CT (CBCT) suite-which can provide both real-time 2D fluoroscopy and 3D CBCT scans for definite visualization of small lesions-has been used more frequently for localizing pulmonary nodules [8,9]. To overcome the limitation of the standard 2D fluoroscopy, we developed a novel technique, termed augmented fluoroscopic bronchoscopy (AFB), using CBCT with an annotation software, which provides both 2D fluoroscopic view and 3D image data, allowing for real-time guidance during bronchoscopic localization [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…As imaging techniques develop so rapidly, using CT has increased greatly in the past few years (1). Many new techniques including CT angiography (CTA), CT perfusion imaging (CTP), and gemstone spectral imaging (GSI) are providing more and more valuable information for clinical diagnosis (2)(3)(4)(5). However, the diagnostic benefits of CT imaging are associated with unavoidable radiation exposure.…”
Section: Introductionmentioning
confidence: 99%